The 4th Syiah Kuala International Conference Conjunction With The 5th Aceh Surgery Update International Conference - Yopie Afriandi Habibie (Journal of International Surgery and Clinical Medicine, 2022)
Assalamualaikum Wr. Wb All Praise and gratitude we pray the presence of Allah SWT for all His grace and guidance so we can still work to help in the fields of education and humanity. With greetings and prayers we praise the prophet rahmatan lil alamin Rasulullah Muhammad SAW who has brought us from the realm of darkness to a realm full of knowledge. This year 2022, we will organized a collaborative event between Faculty of Medicine Universitas Syiah Kuala and Department of Surgery Faculty of Medicine Universitas Syiah Kuala. The event called the The 4th Syiah Kuala International Conference (SKIC) In Conjunction with The 5th Aceh Surgery Update International Conference (ASUIC) 2022. This conference will be delivered a concept as Hybrid Conference will be held on October 6th – 9th 2022, with theme Reconnecting; Advances in Surgery and Clinical Collaboration. This Hybrid conference will be attended by international and national speakers who have expertise in the field of surgery, medical education, clinical medicine and the latest information regarding Medical Education and Health Transformation from Indonesian government. This scientific event felt very special with the presence of the Bali Medical Journal Indexed by SCOPUS (Q4) and Web of Science in scientific publications for all topics presented, both in symposium and free paper sessions. I would like to welcome all experts who are willing to attend in this outstanding hybrid conference to be resource persons at this scientific event, I would like to thank all the committees and sponsors who have helped us to make this activity a success. Finally, I also welcome all the participants, I hope you all get valuable scientific experinces in wonderful city of Banda Aceh. Thank You Sincerely yours, Dr (C). dr. Yopie Afriandi Habibie, Sp. BTKV Sub JD(K) FIHA, FICS, FACS Chairman